Copper-based nano enzyme as well as preparation method and application thereof
By preparing copper-based nanoenzymes (Cu-TA) in the field of food detection, the problems of insufficient enzyme-like activity and poor stability in the prior art are solved, and high sensitivity and selective detection are achieved, which are suitable for multiple application fields.
Patent Information
- Application Number
- CN202411922724.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
AI Technical Summary
When detecting the total antioxidant capacity (TAC) in the prior art, there are problems such as insufficient enzyme-like activity, poor stability, and high cost. In particular, the enzyme-like activity of metal-organic framework (MOFs)-based nanoenzymes is limited, making it difficult to meet the needs of high sensitivity and selectivity.
Polyether F127 is used as a template to coordinate tannin acid with copper ions using formaldehyde cross-linking to prepare copper-based nanoenzymes (Cu-TA) with high catalytic activity and good stability. This nanoenzyme has peroxidase-like activity and is suitable for colorimetric detection of the total antioxidant ability of ascorbic acid and juice.
It realizes high sensitivity and selective detection in the fields of biosensing, food safety analysis, catalytic applications and environmental protection, and has the characteristics of simplicity, fast and real-time detection. The linear range is 0.9-5.4μmol/L and the minimum detection limit is 0.1990μmol/L.
Smart Images

Figure CN119775333A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of food detection technology, and in particular to a copper-based nanozyme and a preparation method and application thereof. Background Art
[0002] In recent years, the development of functional food and medicine is in full swing, among which antioxidant is one of the most important functional demands in the market. Therefore, the total antioxidant capacity of food and medicine is one of the key indicators for evaluating their efficacy. Due to its strong oxidizing property, the Fenton reaction has been used in the degradation of various polymers and has also been applied in TAC detection. Total antioxidant capacity (TAC) refers to the total antioxidant level composed of various antioxidant substances and antioxidant enzymes in the system, such as antioxidant enzymes, vitamin C, vitamin E and carotene. TAC is an antioxidant estimation model that can be used as a comprehensive parameter to evaluate the antioxidant content in actual samples and is also an important indicator for evaluating the quality of antioxidant foods. Ascorbic acid (AA) can be used as a typical antioxidant and is usually used as a representative to evaluate the TAC of various foods, especially beverage samples. AA is a water-soluble vitamin that exists in a variety of fruits and vegetables. It is an essential nutrient for maintaining human health. Sufficient intake of AA is essential for maintaining human health. Therefore, the development of a simple and sensitive AA detection method is of great significance for evaluating the TAC of food.
[0003] Currently reported AA detection methods include electrochemical method, liquid chromatography, fluorescence method and visual sensing method. Among them, visual sensing method has attracted more and more attention due to its high sensitivity, low cost and simple operation. The introduction of new nanomaterials with diverse functions to construct highly sensitive visual sensors has become a research hotspot in the field of TAC analysis. Nanozymes, as a representative nanomaterial, are nanomaterials with activity similar to that of natural enzymes. They have attracted much attention due to their incomparable advantages such as high activity, low cost, good stability, convenient preparation and easy modification. Nanozymes are classified according to enzyme-like activity, including: peroxidase analogs, oxidase analogs, catalase analogs, superoxide dismutase analogs, etc. Among them, a variety of nanomaterials with enzyme-like activity have been used to determine TAC. Chen et al. designed and developed hierarchical porous S / N co-doped carbon nanozymes with enhanced peroxidase activity, using AA as a typical model to determine the total antioxidant capacity of commercial beverages; Zhang et al. used the ABTS colorimetric strategy of gold-doped copper ferrocyanide nanozymes to design a smartphone-based sensor, which was successfully used to determine TAC in plant-derived foods such as lotus root, citrus juice and lemon drinks, promoting the development and utilization of nanozymes in practical detection. LI et al. used highly efficient carbon-loaded Co-Ir peroxidase to determine the total antioxidant capacity of fruits; HAN et al. developed iron-manganese bimetallic oxidase nanozymes to determine the total antioxidant capacity of fruit and vegetable foods. Metal organic frameworks (MOFs)-based nanozymes have made great achievements in the field of nanozyme research due to their good enzyme-like properties and the controllable pore size and surface chemical properties of the materials themselves, ultra-high surface area and porosity, and structural diversity. However, this type of material is easily affected by agglomeration and poor dispersibility, which limits its simulated enzyme activity. Therefore, how to improve the enzyme-like activity of MOF-based nanozymes is one of the difficulties in current TAC detection research. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a copper-based nanozyme with high catalytic activity, good stability, low cost, strong sensitivity and selectivity, simple colorimetric sensing platform components, rapid detection, and convenient real-time detection, which has broad application prospects in the fields of biosensing, food safety analysis, catalytic applications and environmental protection.
[0005] The first aspect of the present application provides a copper-based nanozyme, which uses polyether F127 as a template, and crosslinks tannic acid (TA) with copper ions (Cu) through formaldehyde. 2+ ) are coordinated to obtain a Cu-TA nanomaterial, the surface of the Cu-TA nanomaterial is rough, the four elements of C, N, O, and Cu are evenly distributed, and the loading amounts on the substrate template are 45-55Wt%, 10-18Wt%, 15-24Wt%, and 12-18Wt%, respectively.
[0006] The second aspect of the present application provides a method for preparing a copper-based nanozyme, comprising the following steps: adding ammonia water to a polyether F127 ethanol solution and stirring; then adding tannic acid and formaldehyde solution to the solution, stirring, and then adding Cu 2+ The precursor is stirred for reaction; finally, the product is transferred to a high-pressure reactor, and after high-temperature heat treatment, the obtained metal-tannic acid nanozyme (Cu-TA) is collected by centrifugation and washing.
[0007] The ratio of the polyether F127, water and ethanol is 0.05-0.2 g: 43-49 mL: 5-11 mL.
[0008] The ratio of the amount of ammonia water added to the polyether F127 is 0.5-1 mL: 0.1-0.3 g, and the ammonia solution is 25 wt %.
[0009] The weight ratio of the tannic acid to the polyether F127 is 1:0.8-1.2.
[0010] The ratio of the added amount of formaldehyde to the amount of polyether F127 is 0.35-0.4 mL: 0.1-0.3 g, and the mass fraction of the formaldehyde is 37 wt %.
[0011] The Cu 2+ The weight ratio of the added amount of the precursor to the tannic acid is 1:1.5-2.5.
[0012] In any embodiment, the Cu 2+ The precursor is one of CuCl2·2H2O, Cu(NO3)2 and CuSO4. 2+ The precursor is CuCl2·2H2O.
[0013] The high pressure reactor is hydrothermally treated at 100° C. for 20-28 hours.
[0014] In any embodiment, the preparation method further includes the steps of centrifuging and washing the final product, wherein the washing uses one or a combination of two or more of water, alcohols, ethers and esters; the alcohol is one of ethanol, isopropanol and tert-butanol; the ketone is acetone; the ether is diethyl ether or petroleum ether; the ester is ethyl acetate or ethyl formate; preferably, the washing reagent is anhydrous ethanol.
[0015] In any embodiment, the prepared nanozyme is ultrasonically dispersed in ultrapure water for storage.
[0016] The second aspect of the present application provides an application of a copper-based nanozyme, in which the copper-based nanozyme is used as a peroxidase-like enzyme.
[0017] An application of a copper-based nanozyme, wherein the copper-based nanozyme is used for colorimetric detection of ascorbic acid.
[0018] In any embodiment, when detecting ascorbic acid, the linear range is 0.9-5.4 μmol / L, and the minimum detection limit is 0.1990 μmol / L.
[0019] An application of a copper-based nanozyme, which is used to detect the total antioxidant capacity of fruit juice.
[0020] The concentration of Cu-TA nanozyme in the applied color development system is 32.14 μg / mL, pH is 5.0, and the concentration of H2O2 is 4.46 mM.
[0021] The beneficial effects of the present application: the copper-based nanozyme of the present invention has enhanced peroxidase-like activity, uses AA as a model of antioxidant, has good linearity, low detection limit and high detection sensitivity; it is used for colorimetric detection of ascorbic acid, with a linear range of 0.9-5.4 μmol / L and a minimum detection limit of 0.1990 μmol / L; the copper-based nanozyme of the present invention has great potential for constructing a colorimetric sensing platform with simple, rapid and real-time detection. The detection conditions are close to neutral, closer to the pH of most foods in daily life, convenient for detection, and short incubation time. It will have great application prospects in the fields of biosensing, food safety analysis, catalytic applications and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of Cu-TA in this application.
[0023] Figure 2 This is a high-resolution SEM image of Cu-TA in this application.
[0024] Figure 3 This is the C, N, O, and Cu element mapping spectrum of Cu-TA in this application.
[0025] Figure 4 This is the element distribution diagram of Cu-TA in this application.
[0026] Figure 5 This is a diagram of the catalytic effect of Cu-TA nanozyme on different peroxidase chromogenic substrates in this application.
[0027] Figure 6 The UV-visible absorption spectra of the Cu-TA and blank control reaction systems of this application.
[0028] Figure 7 pH effect diagram of Cu-TA nanozyme catalyzed oxidation of TMB in this application.
[0029] Figure 8This is a diagram showing the effect of Cu-TA nanozyme concentration on the Cu-TA nanozyme-catalyzed oxidation of TMB in this application.
[0030] Fig. 9 This is the effect of H2O2 concentration on the Cu-TA nanozyme-catalyzed oxidation of TMB in this application.
[0031] Fig.10 This is the Michaelis-Menten curve diagram when TMB is used as the substrate in this application.
[0032] Fig.11 This is the Lineweaver-Burk double reciprocal plot when TMB is used as the substrate in this application.
[0033] Fig.12 This is the Michaelis-Menten curve diagram when H2O2 is used as the substrate in this application.
[0034] Fig.13 This is the Lineweaver-Burk double reciprocal plot of this application when H2O2 is used as the substrate.
[0035] Fig.14 This is a diagram showing the effects of three free radical scavengers, tert-butyl alcohol, L-histidine and p-benzoquinone, on the reaction system in this application.
[0036] Fig.15 This is the absorbance graph of the Cu-TA-TMB-H2O2 system with different AA concentrations in this application at 652nm changing with time.
[0037] Fig.16 This is a specific analysis diagram of the colorimetric detection system of the present application for antioxidant detection (the interfering factors are amino acids).
[0038] Fig.17 This is a specific analysis diagram of the colorimetric detection system of this application for antioxidant detection (the interfering factors are inorganic ions and sugars).
[0039] Fig.18 This is the linear relationship between AA concentration and absorbance in this application.
[0040] Fig.19 This is a graph showing the relationship between the absorbance and RGB values of different concentrations of AA in this application.
[0041] Fig. 20 This is a linear relationship diagram between AA concentration and R value in this application.
[0042] Fig.21 This is a graph showing the TAC content in the six fruit juice drinks tested in this application. DETAILED DESCRIPTION
[0043] Below, the copper-based nanozyme of the present application, its preparation method and application implementation method are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] The human body needs to take in natural antioxidants from food to maintain the body's free radical balance. Different antioxidants present in different foods may have synergistic effects, so it is necessary to evaluate the total antioxidant capacity (TAC) in food. TMB (3,3',5,5'-tetramethylbenzidine) can be used as a peroxidase chromogenic substrate in the colorimetric method for the detection of antioxidants. However, the natural peroxidase used in TMB detection has limitations such as low stability and high price. Nanozymes have unique properties of nanomaterials such as high catalytic activity, good stability, and low cost, and have the potential to be used as a substitute for natural enzymes. This application prepares a new type of copper-tannic acid coordination (Cu-TA) nanozyme by studying the method of aldehyde cross-linking, and studies the morphology and elemental composition of the material by scanning electron microscopy (SEM) and X-ray energy dispersive spectrometer (EDS) characterization methods to prove the successful synthesis of the material. Afterwards, its intrinsic peroxidase mimetic activity was verified in the presence of TMB and H2O2, and a TMB and ascorbic acid (AA) color development system for high-sensitivity colorimetric detection of TAC was constructed based on its peroxidase-like activity. Furthermore, by exploring factors such as pH value, H2O2 concentration, and initial nanozyme concentration, the optimal experimental conditions were selected as a final material concentration of 32.14 μg / mL, a buffer pH of 5.0, and a hydrogen peroxide concentration of 4.46 mmol·L -1 , reaction time 5min, incubation temperature 37℃. Simulated enzyme catalytic reaction mechanics showed that the Km values of Cu-TA for substrates TMB and H2O2 were 0.633 and 1.992mM, respectively, and the Vmax values were 7.54×10-8 and 10.85M s -1 , with strong affinity for the substrate. The catalytic mechanism verification shows that during the catalytic process · The generation of OH is the main reason for its excellent peroxidase mimetic activity. The colorimetric sensing platform has a low detection limit (0.1990 μM) and a good linear range (0.9-5.4 μM) in ascorbic acid analysis, with high sensitivity and selectivity, providing practical feasibility for the detection of TAC in commercial beverages. Where μM represents μmol·L -1 .
[0050] A copper-based nanozyme, using polyether F127 as a template, is cross-linked with tannic acid (TA) and copper ions (Cu 2+) are coordinated to obtain a Cu-TA nanomaterial, the surface of the Cu-TA nanomaterial is rough, and the four elements of C, N, O, and Cu are evenly distributed, and the loading amounts of the four elements on the substrate template are 45-55Wt%, 10-18Wt%, 15-24Wt%, and 12-18Wt%, respectively; preferably, the loading amounts of the four elements of C, N, O, and Cu on the substrate template are 50.5Wt%, 14.1Wt%, 19.5Wt%, and 15.9Wt%, respectively.
[0051] Pluronic F-127 was selected because it is a new type of high molecular weight nonionic surfactant that can reduce the nonspecific adsorption of proteins or cells on the surface of the material.
[0052] Cu-TA is spherical, with a rough surface and increased surface area, which exposes more active sites and exhibits excellent enzyme-mimicking activity.
[0053] The second aspect of the present application provides a method for preparing a copper-based nanozyme, comprising the following steps: adding ammonia water to a polyether F127 ethanol solution and stirring; then adding tannic acid and formaldehyde solution to the solution, stirring, and then adding Cu 2+ The precursor is stirred for reaction; finally, the product is transferred to a high-pressure reactor, and after high-temperature heat treatment, the obtained metal-tannic acid nanozyme (Cu-TA) is collected by centrifugation and washing.
[0054] During the reaction, polyether and ethanol are first mixed, and then ammonia water is added. A small amount of ammonia water is added to adjust the pH of the system; then tannic acid is added first, and formaldehyde is added after the tannic acid powder is completely dissolved to ensure that the reaction occurs under liquid phase conditions, making the reaction more complete.
[0055] During the synthesis process, a metal-aldehyde coordination sphere is formed; first, the TA molecules are pre-crosslinked by formaldehyde, which can induce TA polymerization to form TA formaldehyde resin; in a weakly alkaline ethanol / water solution, the polymerization reaction can be well controlled. As a result, low molecular weight PTA oligomers are obtained. Secondly, the PTA oligomers are further aggregated together to form metal-aldehyde spheres through metal-ligand crosslinking. Since TA contains abundant catechol groups, after formaldehyde crosslinking, the PTA oligomers still have enough catechol groups to chelate with metal ions to form coordination polymers. When formaldehyde is not used to crosslink TA, metal-TA coordination rods are synthesized; this may be due to the fast polymerization rate of metal ions and TA. Compared with the formation of polymer rods, formaldehyde crosslinking of polyphenols can weaken the interaction between polyphenols and metal ions by reducing the number of catechol groups. In the present application, the assembly of metal-ligands can be carried out mildly, and thermodynamically stable spheres are obtained.
[0056] The ratio of polyether F127, water and ethanol is 0.05-0.2 g: 43-49 mL: 5-11 mL. The ratio of polyether F127 in water is used to control the size of micelles, thereby forming nanoparticles of a certain size.
[0057] The ratio of the amount of ammonia added to the polyether F127 is 0.5-1 mL: 0.1-0.3 g, and the ammonia solution is 25 wt%. The ammonia is used to adjust the pH of the entire system, making the system alkaline, which is conducive to the polymerization of tannic acid and the coordination of metal ions. Too high or too low ammonia content will affect the formation of polyether F127 micelles.
[0058] The weight ratio of tannic acid to polyether F127 is 1:0.8-1.2. If the relative content of polyether F127 is too high, the polymerization of tannic acid will be insufficient, and if the content is too low, the polymerization of tannic acid cannot be regulated.
[0059] The ratio of the added amount of formaldehyde to the polyether F127 is 0.35-0.4 mL: 0.1-0.3 g, and the mass fraction of the formaldehyde is 37 wt %. By adding a certain concentration and amount of formaldehyde, the morphology of the polymer is regulated to be spherical. Too much or too little will result in other different morphologies, and a spherical structure cannot be formed, or the structure is unstable.
[0060] The Cu 2+ The weight ratio of the precursor to tannic acid is 1:1.5-2.5. 2+ It can be fully coordinated. Too little will lead to metal vacancies, and too much will result in excessive free metal.
[0061] In any embodiment, the Cu 2+ The precursor is one of CuCl2·2H2O, Cu(NO3)2 and CuSO4. 2+ The precursor is CuCl2·2H2O.
[0062] The hydrothermal treatment is carried out in the autoclave at 100° C. for 20-28 hours. The hydrothermal reaction increases the stability of the polymer and prevents easy degradation under acidic conditions; if the reaction time is too short, the obtained polymer is unstable, and if the reaction time is too long, the size of the obtained polymer is too large and affects the overall morphology of the generated polymer.
[0063] In any embodiment, the preparation method further includes the steps of centrifuging and washing the final product, wherein the washing uses one or a combination of two or more of water, alcohols, ethers and esters; the alcohol is one of ethanol, isopropanol and tert-butanol; the ketone is acetone; the ether is diethyl ether or petroleum ether; the ester is ethyl acetate or ethyl formate; preferably, the washing reagent is anhydrous ethanol.
[0064] In any embodiment, the prepared nanozyme is ultrasonically dispersed in ultrapure water for storage.
[0065] The second aspect of the present application provides an application of a copper-based nanozyme, in which the copper-based nanozyme is used as a peroxidase-like enzyme.
[0066] An application of a copper-based nanozyme, wherein the copper-based nanozyme is used for colorimetric detection of ascorbic acid.
[0067] In any embodiment, when detecting ascorbic acid, the linear range is 0.9-5.4 μmol / L, and the minimum detection limit is 0.1990 μmol / L.
[0068] An application of a copper-based nanozyme, which is used to detect the total antioxidant capacity of fruit juice.
[0069] The concentration of Cu-TA nanozyme in the applied color development system is 32.14 μg / mL, pH is 5.0, and the concentration of H2O2 is 4.46 mM.
[0070] Example
[0071] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0072] The main reagents used in this application are shown in Table 1.
[0073] Table 1 Main reagents and manufacturers
[0074]
[0075]
[0076] Example 1
[0077] First, 0.2g of polyether F127 was dissolved in 46mL of water and 8mL of ethanol. 0.5mL of ammonia solution (25wt%) was added and stirred for 1 hour. Then 0.2g of tannic acid was added to the above solution. After the tannic acid was completely dissolved, 0.38mL of formaldehyde solution (37wt%) was added. After stirring for 24 hours, CuCl2·2H2O solution (0.1g CuCl2·2H2O was dissolved in 2mL of water) was added. The reaction was stirred for 24 hours, and the product was transferred to a 100mL high-pressure reactor and hydrothermally treated at 100°C for 24 hours. The obtained metal-tannic acid nanozyme (Cu-TA) was collected by centrifugation and washing. Finally, the prepared nanozyme was ultrasonically dispersed in ultrapure water for use.
[0078] The four elements C, N, O and Cu are evenly distributed, and the loading amounts on the substrate template are 45-55Wt%, 10-18Wt%, 15-24Wt% and 12-18Wt%, respectively.
[0079] The second aspect of the present application provides a method for preparing a copper-based nanozyme, comprising the following steps: adding ammonia water to a polyether F127 ethanol solution and stirring; then adding tannic acid and formaldehyde solution to the solution, stirring, and then adding Cu 2+ The precursor is stirred for reaction; finally, the product is transferred to a high-pressure reactor, and after high-temperature heat treatment, the obtained metal-tannic acid nanozyme (Cu-TA) is collected by centrifugation and washing.
[0080] The ratio of the polyether F127, water and ethanol is 0.05-0.2 g: 43-49 mL: 5-11 mL.
[0081] The ratio of the amount of ammonia water added to the polyether F127 is 0.5-1 mL: 0.1-0.3 g, and the ammonia solution is 25 wt %.
[0082] The weight ratio of the tannic acid to the polyether F127 is 1:0.8-1.2.
[0083] The ratio of the added amount of formaldehyde to the amount of polyether F127 is 0.35-0.4 mL: 0.1-0.3 g, and the mass fraction of the formaldehyde is 37 wt %.
[0084] The Cu 2+ The weight ratio of the added amount of the precursor to the tannic acid is 1:1.5-2.5.
[0085] In any embodiment, the Cu 2+ The precursor is one of CuCl2·2H2O, Cu(NO3)2 and CuSO4. 2+ The precursor is CuCl2·2H2O.
[0086] The high pressure reactor is hydrothermally treated at 100° C. for 20-28 hours.
[0087] Example 2
[0088] First, 0.05g of polyether F127 was dissolved in 43mL of water and 5mL of ethanol. 0.5mL of ammonia solution (25wt%) was added and stirred for 1 hour. Then 0.06g of tannic acid was added to the above solution. After the tannic acid was completely dissolved, 0.35mL of formaldehyde solution (37wt%) was added. After stirring for 24 hours, CuCl2·2H2O solution (0.04g CuCl2·2H2O dissolved in 2mL of water) was added. The reaction was stirred for 24 hours, and the product was transferred to a 100mL high-pressure reactor and hydrothermally treated at 100°C for 20 hours. The obtained metal-tannic acid nanozyme (Cu-TA) was collected by centrifugation and washing. Finally, the prepared nanozyme was ultrasonically dispersed in ultrapure water for use.
[0089] Example 3
[0090] First, 0.1g of polyether F127 was dissolved in 46mL of water and 8mL of ethanol. 1mL of ammonia solution (25wt%) was added and stirred for 1 hour. Then 0.1g of tannic acid was added to the above solution. After the tannic acid was completely dissolved, 0.38mL of formaldehyde solution (37wt%) was added. After stirring for 24 hours, CuCl2·2H2O solution (0.05g CuCl2·2H2O dissolved in 2mL of water) was added. The reaction was stirred for 24 hours, and the product was transferred to a 100mL high-pressure reactor and hydrothermally treated at 100°C for 28 hours. The obtained metal-tannic acid nanozyme (Cu-TA) was collected by centrifugation and washing. Finally, the prepared nanozyme was ultrasonically dispersed in ultrapure water for use.
[0091] Example 4
[0092] First, 0.2g of polyether F127 was dissolved in 49mL of water and 11mL of ethanol. 1mL of ammonia solution (25wt%) was added and stirred for 1 hour. Then 0.24g of tannic acid was added to the above solution. After the tannic acid was completely dissolved, 0.4mL of formaldehyde solution (37wt%) was added. After stirring for 24 hours, CuCl2·2H2O solution (0.04g CuCl2·2H2O dissolved in 2mL of water) was added. The reaction was stirred for 24 hours, and the product was transferred to a 100mL high-pressure reactor and hydrothermally treated at 100°C for 24 hours. The obtained metal-tannic acid nanozyme (Cu-TA) was collected by centrifugation and washing. Finally, the prepared nanozyme was ultrasonically dispersed in ultrapure water for use.
[0093] In addition, the performance of the nanozyme obtained in this application was tested.
[0094] (1) Characterization of Cu-TA
[0095] The morphology and element distribution of nanozymes were characterized by SEM and EDS. Figure 1 It can be seen that the rough surface of Cu-TA material and the increased surface area may be the key to the material's excellent enzyme-mimicking activity. Figure 2 , 3 From the element mapping spectrum, it can be observed that C, N, O, and Cu elements are evenly distributed on the surface of Cu-TA nanomaterials, proving that Cu-TA nanomaterials with good structure and uniform element distribution have been successfully prepared.
[0096] (2) Evaluation of peroxidase-like activity of Cu-TA
[0097] Three common POD enzyme-mimicking chromogenic substrates (TMB, OPD, and ABTS) were selected to investigate the enzyme-mimicking activity of Cu-TA nanomaterials. Figure 5 As shown in the figure, the three substrates were oxidized to blue oxTMB, yellow oxOPD and green oxABTS, and had characteristic absorption peaks at wavelengths of 652, 448 and 416 nm, respectively, indicating that the prepared Cu-TA nanomaterials have enzyme-mimicking catalytic activity and can oxidize peroxidase-like chromogenic substrates. Using TMB as the chromogenic substrate, the peroxidase-like (POD) activity of the synthesized Cu-TA nanozyme was analyzed. The specific steps were as follows: 20 L Cu-TA nanozyme (0.9 mg / mL), 100 L H2O2 (25 mM) and 100 L TMB (10 mM) were added to 780 L NaAc / HAc buffer (100 mM, pH 5.0) in sequence, and the absorbance of the reaction system was recorded using a UV-visible spectrophotometer after incubation at 37 °C for 5 min. In the control experiment, 20 L of 0.9 mg / mL Cu-TA nanozyme was replaced with NaAc / HAc buffer, and the detection process was the same as above. The POD activity of Cu-TA was further verified by monitoring the absorbance value at 652 nm. Figure 6 As shown, TMB and TMB / H2O2 solutions are colorless and have no characteristic absorption peaks. When Cu-TA is added, TMB is oxidized to oxTMB, the solution becomes blue, and has an obvious absorption peak at 652nm, which proves that Cu-TA has POD mimetic enzyme catalytic activity.
[0098] (3) Conditions of Cu-TA catalytic reaction system
[0099] 1) Effect of pH on Cu-TA nanozyme-catalyzed oxidation of TMB
[0100] First, prepare 100mM buffers with different pH values (3.0, 4.0, 5.0, 6.0, 7.0) (where pH = 3.0 is glycine-HCl buffer, and the other pH values (4.0, 5.0, 6.0, 7.0) are NaAc / HAc buffers), then add 5μL Cu-TA (0.9mg / mL), 50μL H2O2 (25mM), 25μL TMB solution (10mM) and 50μL AAA solution (1mM) to 150μL buffers with different pH values. After incubation at 37℃ for 5min, record the absorbance of ox-TMB at 652nm with a microplate reader, and determine the optimal pH using the absorbance as a measurement indicator.
[0101] 2) Effect of Cu-TA concentration on Cu-TA nanozyme-catalyzed oxidation of TMB
[0102] 150 μL NaAc / HAc buffer (100 mM pH 5.0), 5·L Cu-TA nanozymes of different concentrations (0.1 mg / mL, 0.3 mg / mL, 0.6 mg / mL, 0.9 mg / mL, 1.8 mg / mL), 50 μL H2O2 (25 mM), 25 μL TMB solution (10 mM) and 50 μL AA solution (1 mM) were added to the 96-well plate in sequence. The blank control was A0, i.e., 50 μL NaAc / HAc buffer of pH 5.0 was used instead of AA solution, and then the 96-well plate was incubated at 37°C for 5 min, and its absorbance value was immediately recorded to determine the optimal material concentration.
[0103] 3) Effect of H2O2 concentration on Cu-TA nanozyme-catalyzed oxidation of TMB
[0104] 150 μL NaAc / HAc buffer (100 mM pH 5.0), 5·L Cu-TA nanozyme (0.9 mg / mL), 50 μL H2O2 solutions of different concentrations (0, 1, 5, 10, 25, 40, 50 mM), 25 μL TMB solution (10 mM) and 50 μL AA solution (1 mM) were added to the 96-well plate in sequence. The blank control was A0, that is, 50 μL pH 5.0 NaAc / HAc buffer was used instead of AA solution, and then the 96-well plate was incubated at 37°C for 5 minutes, and the absorbance value was immediately recorded to determine the optimal H2O2 concentration.
[0105] Through experiments, it was found that pH had a significant effect on the reaction system. When pH was 5.0, the system had the greatest antioxidant capacity, so the optimal pH was 5.0 ( Figure 7). The effect of Cu-TA nanozyme concentration on the Cu-TA nanozyme catalytic system. The experimental results show that the reaction system has a strong dependence on the concentration of Cu-TA nanozyme and H2O2. The absorbance gradually increases with the increase of nanozyme concentration and H2O2 concentration. Figure 8 As shown in the figure, the antioxidant activity of the system slowly increased when the Cu-TA nanozyme concentration was 1.79-32.14μg / mL, and reached the maximum at 32.14μg / mL. When the Cu-TA nanozyme concentration was higher than 32.14μg / mL, the antioxidant activity began to weaken. This is because at a higher Cu-TA nanozyme concentration, the reduction of AA to the reaction system reached saturation, resulting in a decrease in the antioxidant capacity of the system. In addition, the antioxidant activity of the reaction system began to decrease after the H2O2 concentration reached 4.46mM ( Fig. 9 ). Considering the antioxidant properties of the Cu-TA catalytic system and the appropriate instrument response range, and to avoid the interference of ultraviolet light scattering with the accuracy of the results, a nanozyme concentration of 32.14 μg / mL and a H2O2 concentration of 4.46 mM were used as the optimal dose. In summary, this experiment selected NaAc / HAc buffer at pH 5.0, a Cu-TA nanozyme concentration of 32.14 μg / mL, and a H2O2 concentration of 4.46 mM as the optimal conditions.
[0106] (4) Study on steady-state kinetics of enzyme-catalyzed reactions
[0107] The catalytic reaction rate of nanozymes is affected by the activity of nanozymes. The steady-state kinetics of the enzymatic reaction of Cu-TA nanozymes was studied by changing the concentration of TMB or H2O2. First, the reaction kinetics of Cu-TA nanozymes to the substrate TMB was explored. The concentration of H2O2 was kept constant at 4.46mM, and 200μL NaAc / HAc buffer (100mM pH 5.0), 5·L Cu-TA nanozyme (0.9mg / mL), 50μL H2O2 solution (25mM) and 25μL TMB solution of different concentrations (0.25-20mM) were added to the 96-well plate in sequence. After the solution was mixed, the absorbance of the reaction system at 0s and 60s was immediately recorded. When H2O2 was used as the substrate, the concentration of TMB was kept at 10mM, the concentration of H2O2 was changed (25-600mM), and the detection was carried out under the same test conditions. Record the change of absorbance of the system over time, and calculate the initial reaction rate (V0) according to Formula 2-1 and Formula 2-2. Then, fit it with the Michaelis-Menten equation (Formula 2-3) to make a velocity curve of the initial rate of the enzymatic reaction and the substrate concentration to describe the metabolic kinetics. Make a Lineweaver-Burk double reciprocal curve according to Formula 2-4 and calculate the kinetic parameters.
[0108] A = εbc (2-1)
[0109] V0 = Δc / Δt (2-2)
[0110] Where A is the absorbance at 652nm, au; c is the concentration of the generated substrate, M; b is the thickness of the absorption layer, cm; ε is the molar absorption coefficient of the color-developing substrate, oxTMB is 39000 M·cm -1 ; V0 is the initial reaction rate, M·s -1 .
[0111] V0 = Vmax×[S] / (Km + [S]) (2-3)
[0112]
[0113] Where A is the absorbance change of the reaction system, au; V0 is the initial reaction rate, M·s -1 ; t is the difference in reaction time, s; ε is the molar absorption coefficient of oxTMB (39000 M cm at 652 nm) -1 ), b is the thickness of the absorption layer, cm; Vmax is the maximum reaction speed, M·s -1 ; [S] is the substrate concentration, M; Km is the Michaelis constant.
[0114] like Figure 10-13 As shown in the figure, within the appropriate concentration range of TMB and H2O2, a typical Michaelis-Menten curve was obtained. The Lineweaver-Burk double reciprocal curves of TMB and H2O2 showed that the catalytic reaction conformed to the Michaelis-Menten model, with the calculated Km values being 0.633 and 1.992 mM, respectively, and the obtained Vmax values being 7.54×10-8 and 10.85×10-8 Ms, respectively. -1 . The Km under the action of H2O2 is higher than the Km under the action of TMB, indicating that the affinity of Cu-TA nanozyme for TMB is better than that of H2O2, and the Km of Cu-TA nanozyme for TMB is lower than that of many other nanozymes, indicating that it has good affinity for TMB. In addition, the Vmax of Cu-TA for TMB and H2O2 is close to that of HRP. The above data show that Cu-TA has good affinity and catalytic efficiency for both substrates, indicating that Cu-TA has good pod mimetic activity. It can be used as a better substitute for natural enzymes and some nanozymes for colorimetric detection.
[0115] (5) Study on the catalytic mechanism of Cu-TA as a peroxidase-like enzyme
[0116] The catalytic pathway of peroxidase-like enzymes can be divided into the generation of reactive oxygen species (ROS) and the transfer of electrons. Nanozymes generate ROS under catalysis, such as hydroxyl radicals (·OH), singlet oxygen ( 1 O2), superoxide anion (O2 - ) is the main reason for the observed color change of the reaction solution. Therefore, this study selected TBA, p-BQ and L-His as · OH、O2 - and 1 O2 free radical scavenger, to confirm the possible existence of ROS in the Cu-TA / H2O2 / TMB system, so as to study the catalytic mechanism of Cu-TA as a peroxidase-like enzyme. In the NaAc / HAc buffer (pH5.0, 100mM), 20μL of Cu-TA nanozyme (0.9mg / mL), 100μL of H2O2 (25mM) and 100μL of TMB (10mM) system, 200μL of 10mM different free radical scavengers were added respectively, with a total volume of 1mL, and the mixture was fully mixed and reacted at 37℃ for 5min, and the absorption spectra of each system were immediately recorded.
[0117] Different concentrations of TBA, L-His and p-BQ were introduced into the Cu-TA reaction system to remove · OH, 1 O2 and O2 ·- Through experiments, TBA as · When it was used as a scavenger of OH, it had almost no effect on the reaction system. However, after adding p-BQ, the absorbance of the reaction system decreased significantly, and after adding L-His, the absorbance decreased slightly, indicating that O2·- and a small amount of 1 O2( Fig.14 ).
[0118] (6) Inhibition mechanism and selectivity of Cu-TA nanozyme colorimetric system and colorimetric detection of AA
[0119] like Fig.15 As shown in the figure, when the AA concentration increases, the slope of the curve remains unchanged, but the increase in absorption is delayed. This AA-induced inhibition can be explained by the fact that the hydroxyl radicals produced by the nanozyme are initially more likely to react with AA, resulting in a delay in the TMB color development reaction. However, since the catalyst is not consumed in this process, the slope of the graph is the same as when AA is not added.
[0120] In addition, in order to evaluate the selectivity of the sensor, this experiment selected some potential interfering substances in actual samples to evaluate the anti-interference ability of the system. Figure 16-17, when AA is added, the absorbance of the system will decrease. However, under the same conditions, when other interfering substances with a concentration of 5 times that of AA are added, these interfering substances have almost no effect on the system, proving that the system exhibits a more comprehensive antioxidant capacity analysis. It can be seen that the colorimetric sensing platform has a strong anti-interference ability and has a strong stability in the detection of reducing substances, and can be used to detect TAC in food.
[0121] The antioxidants can consume free radicals and inhibit TMB oxidation, thereby realizing the detection of AA. The specific detection method is as follows: NaAc / HAc buffer (100mM) at pH 5.0, 5μL Cu-TA (0.9mg / mL), 50μL H2O2 (100mM), 25μL TMB solution (5mM) and 50μL AA solutions of different concentrations are sequentially added to a 96-well plate. After incubation at 37°C for 10 minutes, the absorbance value A at a wavelength of 652nm is recorded. The blank control is A0, that is, 50μL NaAc / HAc buffer at pH 5.0 is used to replace the AA solution, and a standard curve of AA concentration and absorbance is established. Fig.18 It can be seen that there is a good linear relationship between AA concentration and absorbance in the range of 0.005-0.03 mM, with a linear correlation coefficient (R2) of 0.9965, and the detection limit (LOD) is 0.0012 mM calculated based on a 3-fold signal-to-noise ratio. In summary, the colorimetric sensing system established in this study has good sensitivity for the detection of antioxidant AA.
[0122] (6) Total antioxidant capacity test
[0123] Since TAC can also prevent the action of free radicals at low concentrations, it can be used as a model for estimating antioxidants and calculating the comprehensive parameters of antioxidants contained in actual samples. Therefore, TAC is becoming an important antioxidant biomarker for monitoring the health of organisms. AA was selected as a model of antioxidants, which can effectively inhibit the color development reaction of TMB-H2O2 catalyzed by Cu-TA, which provides favorable conditions for evaluating the TAC level in fruit juice drinks using the above-mentioned sensor system. In addition, a smartphone-based TAC detection platform was established. A smartphone was used to collect the colors of the test solutions containing different concentrations of ascorbic acid, and then the ImageJ software was used to convert the collected different colors into RGB values. The R value of the obtained RGB model changed most significantly with the change in absorbance (such as Fig.19 ). By connecting the R value, absorbance and AA concentration, it was found that there was a good linear relationship between AA concentration and R value ( Fig. 20 ). Therefore, the total antioxidant capacity in juice can be analyzed conveniently using a smartphone without the need for large equipment.
[0124] This application uses AA as a typical model of antioxidants to analyze TAC in fruit juice drinks (orange juice, apple juice, grape juice, grapefruit juice, prune juice, pomegranate juice). The content of TAC in the sample is measured based on the result calculated by the AA standard curve. In order to make the test results conform to the linear range of AA, the sample is diluted a certain multiple with ultrapure water, replaced with the AA standard sample, and analyzed under the same conditions. The TAC in the actual samples was detected and analyzed. The TAC contents in pomegranate juice, orange juice, prune juice, grape juice, grapefruit juice, and apple juice were 306.86μM, 616.81μM, 2022.03μM, 918.26μM, 964.64μM, and 271.98μM, respectively ( Fig.21 ).
[0125] This application selects ascorbic acid (AA) as a model of antioxidants. A smartphone can be used to collect the colors of the solutions to be tested containing different concentrations of ascorbic acid, and then the collected different colors are converted into RGB values using ImageJ software. The R value of the obtained RGB model changes most significantly with the absorbance. The R value, absorbance, and AA concentration are connected, and there is a good linear relationship between the AA concentration and the R value. Therefore, the total antioxidant capacity in the juice can be easily analyzed using a smartphone without the use of large equipment.
[0126] The present invention prepares Cu-TA nanozyme by aldehyde cross-linking and hydrothermal method, which can catalyze the production of · OH and a small amount of O2·-reactive oxygen species, and then oxidized the color substrate to change color, showing excellent POD catalytic activity. The effects of different pH values, different Cu-TA nanozyme concentrations and different H2O2 concentrations on the Cu-TA / H2O2 / TMB color system were compared, and the optimal reaction conditions were selected as pH 5.0, Cu-TA nanozyme concentration of 32.14μg / mL, and H2O2 concentration of 4.46mM. The steady-state kinetic study of the enzymatic reaction showed that Cu-TA had good affinity and catalytic efficiency for both TMB and H2O2 substrates. At the same time, the colorimetric sensor has strong anti-interference performance. Based on the good enzyme-like catalytic activity of Cu-TA nanozyme, a colorimetric sensing platform for detecting antioxidants was constructed. The AA concentration showed a good linear relationship with the absorbance in the range of 0.9-5.4μmol / L, and the LOD was 0.1990μmol / L. Taking AA as the antioxidant model, a smartphone-based TAC detection platform was established, and the TAC content in six fruit juice drinks (pomegranate juice, orange juice, prune juice, grape juice, grapefruit juice, and apple juice) was successfully determined. The nanozyme-based colorimetric sensing platform constructed in this work has the characteristics of simplicity, rapidity, and real-time detection, and will have great application prospects in the fields of biosensing, food safety analysis, catalytic applications, and environmental protection.
[0127] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A copper-based nanozyme, characterized in that: Using polyether F127 as a template, tannic acid (TA) and copper ions (Cu) were cross-linked by formaldehyde. 2+ ) are coordinated to obtain a Cu-TA nanomaterial, the surface of the Cu-TA nanomaterial is rough, the four elements of C, N, O, and Cu are evenly distributed, and the loading amounts on the substrate template are 45-55Wt%, 10-18Wt%, 15-24Wt%, and 12-18Wt%, respectively.
2. A method for preparing a copper-based nanozyme, comprising the following steps: adding ammonia water to a polyether F127 ethanol solution and stirring; then adding tannic acid and formaldehyde solution to the solution, stirring, and then adding Cu 2+ The precursor is stirred for reaction; finally, the product is transferred to a high-pressure reactor, and after high-temperature heat treatment, the obtained metal-tannic acid nanozyme (Cu-TA) is collected by centrifugation and washing.
3. The preparation method according to claim 2, characterized in that: The ratio of the polyether F127, water and ethanol is 0.05-0.2g:43-49mL:5-11mL; the ratio of the added ammonia water to the polyether F127 is 0.5-1mL:0.1-0.3g, and the ammonia solution is 25wt%.
4. The preparation method according to claim 2, characterized in that: The weight ratio of tannic acid to polyether F127 is 1:0.8-1.2; the ratio of the added amount of formaldehyde to polyether F127 is 0.35-0.4 mL: 0.1-0.3 g, and the mass fraction of formaldehyde is 37 wt%.
5. The preparation method according to claim 2, characterized in that: The Cu 2+ The weight ratio of the precursor addition amount to tannic acid is 1:1.5-2.5; the Cu 2+ The precursor is one of CuCl22H2O, Cu(NO3)2 and CuSO4.
6. The preparation method according to claim 2, characterized in that: The high pressure reactor is hydrothermally treated at 100° C. for 20-28 hours.
7. An application of a copper-based nanozyme, using the copper-based nanozyme as a peroxidase-like enzyme.
8. An application of a copper-based nanozyme, using the copper-based nanozyme for colorimetric detection of ascorbic acid.
9. An application of copper-based nanozyme, using copper-based nanozyme to detect the total antioxidant capacity of fruit juice.
10. The use according to any one of claims 7 to 9, characterized in that: The concentration of Cu-TA nanozyme in the applied color development system is 32.14 μg / mL, pH is 5.0, and the concentration of H2O2 is 4.46 mM.